Lingual nerve injuries: recognized complications or preventable errors? - Van der Cruyssen, Frederic; Willaert, Robin; Miloro, Michael (Frontiers in Oral Health, 2025)
Lingual nerve injuries (LNIs) represent a significant clinical challenge that can compromise speech, taste perception, and overall patient well-being. These may occur during third molar extractions, inferior alveolar nerve blocks, implant placement, root canal treatment and other dental, oral, and maxillofacial procedures. A major controversy centers on whether LNIs should be regarded as recognized complications—unavoidable events despite competent care—or potential negligence arising from substandard practice. Such classification hinges on factors including adherence to standard surgical protocols, informed consent, and timely postoperative assessment. Early detection using both qualitative and quantitative sensory evaluations allow prompt referral for microsurgical intervention, potentially improving outcomes if repairs are done within six months of injury. Conversely, lapses in diagnosis or management can lead to enduring disability, increased legal risk, and allegations of negligence. Evolving guidelines and advances in imaging and artificial intelligence may ultimately refine risk assessments, reduce complications, and alter standards of care. By recognizing the multifactorial nature of LNIs and adhering to rigorous surgical protocols, continuing education, and thorough documentation, healthcare professionals can optimize patient safety and potentially mitigate medico-legal challenges and enhance patient outcomes.